1998
DOI: 10.3171/jns.1998.88.4.0734
|View full text |Cite
|
Sign up to set email alerts
|

Distribution and stability of antisense phosphorothioate oligonucleotides in rodent brain following direct intraparenchymal controlled-rate infusion

Abstract: The authors found that PS-ODNs can be safely delivered in high concentrations to wide areas of rat brain by using high-flow microinfusion and are stable even after 48 hours in situ.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(19 citation statements)
references
References 29 publications
3
16
0
Order By: Relevance
“…To achieve uniform and reproducible results, we employed a slow and rate-controlled positive pressure pump that we have used previously to deliver antisense oligonucleotides into the brain of Fischer 344 rats. 23 We found that 5 ϫ 10 9 PFU of Ad␤gal in a volume of 150 L and infused at a rate of 1 L/minute was the most efficient condition for virus delivery compared with the same dose of virus in either 50 or 3 ϫ 50 L, as determined by ␤-gal staining of tumor sections (Fig 6). Using this procedure, we were able to achieve 40% infection of the tumor, whereas 50 and 3 ϫ 50 L produced 5% and 25% infection, respectively.…”
Section: Rat Rt2 Cells Express Low Levels Of CDmentioning
confidence: 77%
“…To achieve uniform and reproducible results, we employed a slow and rate-controlled positive pressure pump that we have used previously to deliver antisense oligonucleotides into the brain of Fischer 344 rats. 23 We found that 5 ϫ 10 9 PFU of Ad␤gal in a volume of 150 L and infused at a rate of 1 L/minute was the most efficient condition for virus delivery compared with the same dose of virus in either 50 or 3 ϫ 50 L, as determined by ␤-gal staining of tumor sections (Fig 6). Using this procedure, we were able to achieve 40% infection of the tumor, whereas 50 and 3 ϫ 50 L produced 5% and 25% infection, respectively.…”
Section: Rat Rt2 Cells Express Low Levels Of CDmentioning
confidence: 77%
“…Antisense oligonucleotide and the drug directly injected into brain with high-flow microinfusion can be safely delivered at high concentration to wide areas of rat brain, bypassing the blood-brain barrier and avoiding the implications after systemic administration (24,25). Clinical trials of this drug in humans have been discouraging (26,27).…”
Section: Discussionmentioning
confidence: 99%
“…Unmodified phosphodiester oligodeoxynucleotides remain intact after incubation in CSF ex vivo for up to 24 h (Whitesell et al 1993). Accordingly, unmodified oligodeoxynucleotides injected intracerebrally were shown to be rapidly degraded and to disappear within 24 h from the injection site, whilst phosphorothioate oligodeoxynucleotides remained stable and could be detected after 48 h post injection (Szklarczyk & Kaczmarek, 1995;Broaddus et al 1998). The tissue penetration of phosphorothioate AS ODNs infused either intrastriatally or i.c.v.…”
Section: Experimental Controlsmentioning
confidence: 99%
“…injections is the use of osmotic minipumps, enabling continuous infusion for several days Broaddus et al 1999). Intraparenchymal controlled-rate infusion has also been employed (Broaddus et al 1998). Examples of doses of AS ODNs and modes of intracerebral delivery are provided in recent reviews Weiss et al 1997;Phillips, 1997).…”
Section: Experimental Controlsmentioning
confidence: 99%